1989
DOI: 10.1093/nar/17.11.4061
|View full text |Cite
|
Sign up to set email alerts
|

Mutant analysis of protein interactions with a nuclear factor I binding site in the SL3-3 virus enhancer

Abstract: Nuclear factor I (NFI) is shown to be of importance for the activity of the enhancer element of a T-cell leukemogenic murine retrovirus, SL3-3, and for the regulation of this element by glucocorticoid. Each nucleotide of the binding site of the NFI proteins was mutated, and the effects of the mutations were quantitated with an electrophoretic mobility shift assay. Mutations in the inverted repeat of the binding site have symmetric effects which strongly support the notion that NFI proteins preferentially bind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 56 publications
3
41
0
Order By: Relevance
“…Another protected region observed in the in vitro study and centered at position -130 is also seen in vivo {footprints III and IV); however, the most prominent reactivity differences are seen at the left-most boundary{-140 to -155}. The region of footprint IV shows a significant homology to a high-affinity NF1-binding site (Nilsson et al 1989}. Two guanosines of the CCAAT element at position -108 are also protected {footprint III).…”
Section: Genomic Sequencing Of An X-linked Cpg Islandmentioning
confidence: 69%
“…Another protected region observed in the in vitro study and centered at position -130 is also seen in vivo {footprints III and IV); however, the most prominent reactivity differences are seen at the left-most boundary{-140 to -155}. The region of footprint IV shows a significant homology to a high-affinity NF1-binding site (Nilsson et al 1989}. Two guanosines of the CCAAT element at position -108 are also protected {footprint III).…”
Section: Genomic Sequencing Of An X-linked Cpg Islandmentioning
confidence: 69%
“…The dimensions of this footprint were previously difficult to ascertain by DMS footprinting (Pfeifer et al 1990a), as only a few of the guanosines showed differential reactivity when compared with naked DNA. This region contains two sequences with homology to the binding site of transcription factor NF1 {TGGCA-binding protein; Nilsson et al 1989 and references thereinl. The boundaries of this footprint were resolved more clearly with a primer set located farther upstream (Fig.…”
Section: Dnase I Footprints On the Xa And A Comparison Of Naked Dna mentioning
confidence: 99%
“…The overlapping GRE/Egre site sequence AGAACAGATGGTCCC (the E-box is highlighted) is highly conserved among murine gammaretroviruses (27) but is not found in cellular genes. The glucocorticoid induction of the SL3-3 enhancer is less significant in T cells than in HeLa cells, which are scarce in bHLH factors (10,11,29,52). This indicates that bHLH factors occupy Egre in T cells and, hence, that the GRE does not play a main role for SL3-3 enhancer activation in T cells.…”
mentioning
confidence: 95%
“…Runx and c-Myb binding sites are critical for tumor induction by 30,51,60), whereas Ets and NF-1 sites are less important (19,21,22,51,52,59,60). Besides significantly weakening the virus, the mutations of all Runx sites in the SL3-3 transcriptional enhancer (the SL3-3dm mutant) were found to shift disease patterns from exclusively T-cell lymphomas to various hematopoietic malignancies, including B-cell lymphomas and myeloid and erythroid leukemias (57).The roles of the glucocorticoid response element (GRE) and bHLH binding E-box motifs in tumor induction by SL3-3 have not been investigated; however, the binding of GR and bHLH factors affects SL3-3 transcriptional activity (10,11,29,49,50,52). E-box binding proteins belong to the large diverse group of bHLH proteins that are involved in cell cycle control, cell lineage development, and tumorigenesis (1-4, 16-18).…”
mentioning
confidence: 99%
See 1 more Smart Citation